W2P: A high-power integrated generation unit for offshore wind power and ocean wave energy. (1st December 2016) - Chen, Weixing; Gao, Feng; Meng, Xiangdun; Chen, Bin; Ren, Anye
Abstract: Energy resources of offshore wind and ocean wave are abundant, clean and renewable. Various technologies have been developed to utilize the two kinds of energy separately. We present a high-power integrated generation unit for offshore wind power and ocean wave energy (W2P). The unit includes that: (1) The wind wheel with retractable blades and the 3-DOF (degrees of freedom) mechanism with the hemispherical oscillating body are used to collect the irregular wind and wave power, respectively; (2) The energy conversion devices (ECDs) are utilized to convert mechanical energy from both the wind wheel and the 3-DOF mechanism into hydraulic energy; (3) The hydraulic energy is used to drive the hydraulic motors and electrical generators to produce electricity. Some analyses and experiments have been conducted to obtain the performance of the key components of the unit. Based on the layout method, the single row wind-wave power plant is established. Highlights: A high-power integrated generation unit for offshore wind power and ocean wave energy (W2P) is proposed. The principle and performance of the unit are presented. The wind-wave power plant based on the unit is established.